Economics of Music Industry – Revenue Streams of the Artists - Paweł KOSSECKI1; Andrzej KARP2; Oguzhan AKIN3; Karolina PŁONECZKA4; Dominika NAROŻNA5 (Communications of International Proceedings, 2021)
Objectives: Artists and performers are generally incentivised by the ownership of their work. Their income is generated based on the related rights and neighbouring rights. However, the economics of the copyright studies has excluded the most essential link between artists and their source of artistic and intellectual production, namely the net income that determines their stability. In such a subjective industry, problems of the rights holders should be described from their perspective to bring fundamental solutions and innovation. Background: In the literature, the economic relations of the Collective Management Organizations (CMOs) and digital platforms with copyright users are largely researched. The net income for the copyright holders are either rarely estimated or mostly ignored. Therefore, this exploratory research brings to conventional studies on the economics of copyright the most crucial perspective regarding on the industry’s contribution to its sustainability. Data/Methods: The research consisted of interviews with artists and performers, who were randomly selected from databases of CMOs (ZAIKS, Stoart) and social media, using pre-defined online surveys consisting of closed questions designed to study explore the economics of copyright from the artists’ perspective.  In  total 40 questions have been stated, they were divided into 4 categories each consisting 10 questions. These categories include the perspective on producers/service companies, the perspective on intermediaries (such as CMOs, Digital Platforms etc.), perspective on governments and perspective on regulators/regulations/law. The survey design within each of main themes asked their overall relationship status with the stakeholder in question, including their need in relation to the added value they bring to the wellbeing of artists, as well as their shortcomings that ultimately result in the loss of potential income for artists and their support in catastrophic situations such as the Covid-19 pandemic. Results were evaluated using taxonomic methods with multivariate comparative statistical analysis. Expected Results: The findings explain the need for industry transparency within a better regulatory environment through supportive and protective government guidance in the light of the Covid-19 pandemic crisis and its impact. Policy Implications: We strongly believe that state support for the intellectual property rights of artists and performers must be strictly regulated. Moreover, the perspective of assessing their way of working with possible irregularities should be separated from the conventional way of thinking about work. A wide range of services should be considered in advance, from a stable social security framework to easily accessible funds for their needs.
Keywords: copyright economics; directives; intellectual property; valuation of copyrights; finance of the music; copyrights; moral rights; cultural economics; regulations; finance of creative industries.